Indacaterol for chronic obstructive pulmonary disease: systematic review and meta-analysis. - Vincent C H Chung; Polly H X Ma; David S C Hui; Wilson W S Tam; Jin Ling Tang (PLoS ONE)
Background Inhaled bronchodilators are the first-line therapy for COPD. Indacaterol is a novel addition to existing long-acting bronchodilators. Objectives Systematic review of randomized controlled trials (RCT) ON efficacy and safety of indacaterol as compared: 1) with placebo at different dosages, 2) with existing bronchodilators; (3) as add-on treatment to tiotropium. Methods We searched 13 electronic databases, including MEDLINE, EMBASE and CENTRAL, and contacted the manufacturer for unpublished data. Primary outcome was mean FEV1 change at 12(th) week, secondary outcomes included changes in SGRQ, TDI and BODE index at 6 months, exacerbation at 1 year, and worsening of symptoms. Results Twelve eligible RCTs of moderate risk of bias included data from 10,977 patients. Compared to placebo, indacaterol improved FEV1 by a weighted mean difference (WMD) of 0.16 L (95%CI: 0.15, 0.18 L, p<0.001), homogeneously above the minimally important difference of 0.10 L. It offered clinically relevant improvement in all secondary outcomes except exacerbation. Magnitude of benefit did not differ significantly by dosage, but one treatment related death was reported at 300 ug. Efficacy of Indacaterol was similar to formoterol and salmeterol (FEV1 WMD = 0.04 L, 95%CI: 0.01 L, 0.07 L, p = 0.02); and tiotropium (FEV1 WMD = 0.01 L, 95%CI: -0.01, 0.03 L, p = 0.61). The use of indacaterol on top of tiotropium yielded additional improvement on FEV1 (WMD = 0.07 L, 95%CI: 0.05 L, 0.10 L, p<0.001). Conclusion Indacaterol is safe and beneficial for patients with COPD at dosage ≤150 ug. It may serve as a good alternative to existing bronchodilators, or as an add-on to tiotropium for unresponsive patients. Use of higher dosage requires further justification.